Expression of Bcl-2 in Inflammatory Sites from Patients with Active Behçet's Disease - K. Hamzaoui; A. Hamzaoui; L. Zakraoui; A. Chabbou (Mediators of Inflammation)
Behçet's disease (BD) is a current systemic vasculitis of unknown aetiology. Eyes, skin, joints, the oral cavity, genital system, blood vessels, central nervous system and lung are usually involved. Defective regulation of programmed cell death (apoptosis) may play a role in the development of (BD), and the protooncogene Bcl-2 is involved in the control of apoptosis in immunocompetent cells. We therefore wished to investigate the expression of Bcl-2 in the peripheral lymphocytes and in two inflammatory sites of patients with active BD: bronchoalveolar lavage (BAL) and cerebrospinal fluid (CSF) lymphocytes. Levels of Bcl-2 expression in the lymphocytes of patients with BD and, for comparison, in the lymphocytes of healthy controls and non-inflammatory neurological diseases (NIND), were studied by two-colour cytofluorography and RNA analysis. In BD patients, a significant proportion of T cells expressed increased amounts of Bcl-2 protein, both in peripheral blood and in inflammatory sites. Mononuclear cells of patients with BD showed increased amount of Bcl-2 messenger RNA. The in vitro incubation of T lymphocytes with IL-10, significantly increased the Bcl-2 expression, specifically in T lymphocytes from inflammatory sites. In active BD, stimulation of HSV-1 T lymphocytes slightly increased Bcl-2 expression, not significantly different from unstimulated HSV-1 T cells. The occurrence of circulating T lymphocytes with abnormally high Bcl-2 expression in peripheral circulation and in inflammatory sites may be explained in part by the increased in vivo activation levels, and by aetiopathological agent(s): our findings seem to indicate an important role in the chronic inflammation in BD.